A comparison of preincisional and postincisional ultrasound guided transversus abdominis plane block - Emy Ambooken; Joe John Chirayath; P Raghavan (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Transversus abdominis plane blocks are part of the multimodal analgesia used for lower abdominal surgeries.Our aim of this study was to compare the analgesic efficacy of preincisional and postincisional TAP blocks in patients undergoing total abdominal hysterectomies. Material and Methods: 54 American Society of Anesthesiologists physical status I and II patients aged between 30 and 60 years who underwent a total abdominal hysterectomy under spinal anesthesia in our hospital were chosen for the study. Alternate patients satisfying the inclusion criteria were either given a preincisional or postincisional transversus abdominis plane block bilaterally. Postoperatively, the numeric pain intensity scale was observed, along with nausea, vomiting, and sedation scores. Results: Pain scores were significantly lower (P < 0.05) in the preincisional TAP block group from the 2nd postoperative hour onwards till 12 h, and thereafter it was comparable between both the groups. The total morphine requirement was significantly less in the preincisional TAP group (P-value 0.001). Also, the mean time to the first request for morphine was significantly longer in patients belonging to the preincisional TAP block group (P-value of 0.002). There were no significant differences in the sedation scores postoperatively, except at the 4th hour, where it was significantly higher (P-value of 0.024) in the postincisional TAP group. Post operative nausea and vomiting was significantly higher and so the dose of the antiemetic used was also observed to be more in the postincisional TAP block group. Conclusion: Preincisional TAP blocks are more effective than postincisional ones with better analgesia and lesser side effects, for total abdominal hysterectomies.